Teledermatology in a Rural Family Practice - D. O'Mahony; L. Banach; D.H. Mahapa; E.W. Lancaster; G.D. van der Linde; B.H. Williams; R.F. Herring; S.A. Asvadi (South African Family Practice)
Background: Telemedicine can provide specialist services at a distance to rural areas where access to such services is limited, especially in developing countries. The objectives of this study are to describe and evaluate a teledermatology service in a rural family practice.